The Subjectivity of Sex(ual Inclusion) - Theron, Shirah (The Stellenbosch Socratic Journal, 2021)
The term ‘sexual inclusion’ is commonly taken to refer to the adjustment of our social and educational practices to counteract prejudices that are connected to sex. The project of sexual inclusion can be used, for example, to advocate against the discrimination of the LGBTQIA+ (lesbian, gay, bisexual, trans, queer, intersex, asexual, ally and others) community or certain unconventional BDSM (bondage and discipline, dominance and submission, sadism, and masochism) dynamics and activities. This essay, however, takes sexual inclusion as the project that promotes the equal and largely indiscriminatory opportunity for each person to engage in meaningful and pleasurable nonmorally good sexual experiences, because, as I will argue, sex is part of what it means to live a flourishing and good human life. This essay focuses specifically on nonmorally good sex, how we experience it, and its fundamental role in promoting sexual inclusion – if one does not experience nonmorally good sex, one cannot feel or be considered as being sexually included. To have a better grasp on the project of sexual inclusion and what it is, I discuss the different mechanisms that can lead to sexual exclusion and how experiencing sexual exclusion can hinder our progress towards living a good and flourishing life. I conclude that due to its subjective nature, the experience of nonmorally good sex itself challenges and limits us in our pursuit of the advancement and achievement of sexual inclusion. Engaging in a sexual activity with another person due to the motivating reasons to provide that person with a nonmorally good sexual experience (with the goal of advancing their sexual inclusion), is not an input-output kind of process. If we are unable to guarantee nonmorally good sex for others, the result is that we cannot guarantee their sexual inclusion either.